Conservation and variation of structure and function in a newly identified GCM homolog from chicken - Wegner, Michael; Hashemolhosseini, Said; et al. (Journal of Molecular Biology, 2004)
Glial cell missing (GCM) proteins constitute a small family of transcription factors with two members each described in Drosophila and several mammalian species. Here, we report the identification of a GCM homolog from chicken. Although the exon-intron structure is well conserved between chicken GCM and other family members, sequence similarity is largely restricted to the DNA-binding GCM-domain (residues 24-176). In accord with the high degree of sequence conservation within the GCM-domain, the chicken GCM protein has a DNA-binding specificity similar to that of other GCM proteins. Like other GCM proteins, it is located to the nucleus and can act as a transcriptional activator despite the strong divergence in sequences outside the GCM-domain. The chicken GCM protein contains two transactivation domains with cell-specific function, one immediately following the DNA-binding domain, the other at its extreme carboxy terminus. Intriguingly, chicken GCM is expressed only transiently during embryogenesis and is restricted exclusively to extraembryonic tissues where it was detected in close vicinity to embryonic blood vessels. Taking the extraembryonic expression of chicken GCM and mammalian GCMa into account, it is tempting to speculate that a conserved extraembryonic function exists for GCM proteins in birds and mammals. © 2003 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2004.med.IB.LPCIPDBI.conser
Keywords: Gcm-1; GCMa; Glial cells missing; Placenta